2017
DOI: 10.1111/1750-3841.13639
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Experiment: Using Immersive Technologies to Study the Impact of “All‐Natural” Labeling on Perceived Food Quality, Nutritional Content, and Liking

Abstract: The "all-natural" label is used extensively in the United States. At many point-of-purchase locations, employed servers provide food samples and call out specific label information to influence consumers' purchase decisions. Despite these ubiquitous practices, it is unclear what information is conveyed to consumers by the all-natural label or how it impacts judgments of perceived food quality, nutritional content, and acceptance. We used a novel approach incorporating immersive technology to simulate a virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…These findings are consistent with the positive opinions consumers sometimes associate with food labels without standardized interpretations or with ambiguous claims such as "All Natural" (Liu et al 2017). What appears obvious, however, is that consumers' response may be stronger towards labels that highlight a contaminant they wish to avoid.…”
Section: Preferences For Ground Beef Labelssupporting
confidence: 85%
“…These findings are consistent with the positive opinions consumers sometimes associate with food labels without standardized interpretations or with ambiguous claims such as "All Natural" (Liu et al 2017). What appears obvious, however, is that consumers' response may be stronger towards labels that highlight a contaminant they wish to avoid.…”
Section: Preferences For Ground Beef Labelssupporting
confidence: 85%
“…Amos, Pentina, Hawkins, & Davis (2014) suggested that food products labeled with natural claims are perceived to be less harmful and healthier, with superior instrumental attributes, and possessing higher nutritional value and lower human contamination. Liu, Hooker, Parasidis, & Simons (2017) found that the presence of an all-natural FOP label improves consumers' perceptions of product quality and nutritional content. Finally, suggested that perceived risk represents an important instrumental reason for naturalness preference.…”
mentioning
confidence: 97%
“…Among situational factors, the perception of naturalness depends also on the type of stores, because some of them convey a sense of naturalness, such as traditional markets, leading to more perceived naturalness . In addition, Liu et al (2017) found that the additional Please cite as: Asioli, Daniele; Aschemann-Witzel, Jessica; Caputo, Vincenzina; Vecchio, Riccardo; Annunziata, Azzurra; Naes, Tormod; Varela, Paula. Making sense of the ''clean label'' trends: a review of consumer food choice behavior and discussion of industry implications Food Research International, 99, 58-71. https://doi.org/10.1016/j.foodres.2017 28 information provided by employed servers at the point of purchase impacts consumers' perceptions of quality and nutritional content of all-natural labelled products.…”
mentioning
confidence: 99%
“…2018, Liu et al. 2017), both of which can influence consumption. In the present research, participants chose the granola bowl to eat with label descriptor that was the most “natural” to them.…”
Section: Resultsmentioning
confidence: 99%
“…However, from a list of 20 ingredients, not one was considered “natural” by >69% of respondents (Chambers, Chambers, & Castro, 2018). When queried about the expected meaning of “natural,” answers related closely to the absence of additives or little human intervention (Liu, Hooker, Parasidis, & Simons, 2017). A systematic review revealed that “naturalness” is important to a majority of consumers across countries, independent of the years in which research was performed; however, inconstancies in how “naturalness” was defined or measured make it difficult to ascertain the decision‐making attributes of a food or ingredient that consumers determine as natural (Roman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%